PENGEMBANGAN KAWASAN PASCA PERTAMBANGAN TIMAH: PENDEKATAN KONSEP ECO-DEVELOPMENT - Rustam Hakim Manan; Quintarina Uniaty (http://arl.faperta.ipb.ac.id/, 2011)
Eco development gave top priority to considerationsin sustainable development. An approachment need to be applied in environmentally prospective on spatial planning, by integrating sub sistem of planning aspects whichemphasizes on ecosystem and prediction on its success in order to integrate objectives in economy, social-cultural and environmental. Ex-mining sites in Indonesia need a primary attention due to the environmental damages they caused, by means of reclamation as an effort to restore and increase the quality of its natural resources. Primary consideration in its developing concept is the improving of regional quality with concistency in keeping local potention and characteristic in functional and aesthetic considerations; and give a positive impact for society in ecology, economy, social and cultural. Landscape planning as a developing idea fully responsible to realize the success of exploitation and development of ex-mining sites. Pantai Tanjung Tinggi in Bangka Belitung were choosen as a sample case of post-mining site planning through strategic approachment for a development of beach recreational site, Eco-park; a New Landscape in ex-mining Development based on sustainable local wisdom.